Sustainable Automotive Technologies 2011 Proceedings of the 3rd International Conference - Hung, Steve; Subic, Aleksandar; Wellnitz, Jörg (Springer Berlin Heidelberg : Imprint: Springer, 2011)
These proceedings capture papers presented at the third International Conferences on Sustainable Automotive Technologies (ICSAT), held at the Clemson University International Center for Automotive Research (CU-ICAR), Greenville, South Carolina, USA, during 5-6 April 2011. ICSAT is the state-of-the-art conference in the field of new technologies for transportation. The book summarizes all important trends in sustainability of automotive development today with a special focus on materials, propulsion technologies as well as manufacturing issues. It provides a brief selection of papers and key-note speakers of the conference. Papers from the US, Australia, Europe and Asia are showing the lighthouse character of the conference, in a field which gains more and more importance as far as emissions and the lack of fossil fuels in the future are concerned. The book provides a very good overview of R&D activities at OEMs as well as in leading universities and laboratories; the special focus is on new ideas for sustainable mobility.